MODEL DEVELOPMENT OF FACTORS THAT INFLUENCE WORK-LIFE BALANCE - Hanifa Sari, Dini
Everyone needs a balance between work life and personal life. Balancing work life balance is not easy. Therefore, the problem of work-life balance becomes an important issue for management in various organizations. Employees do not want to work in organizations that do not support work-life balance. This research studies several factors that affect work-life balance which are expected to obtain job satisfaction for employees. These factors include job control, job demands, and job stress. The object of research is permanent employees in state-owned enterprises, private companies, state ministries and state institutions. Data processing was performed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique using SmartPLS software. Data processing is tested through measurement models and structural model evaluations. The results showed that job control does not have significant effect on work-life balance but have an effect on job stress. This implies that job control affects work-life balance through mediation from job stress. Job demands and job stress affect work-life balance significantly. Job stress significantly affects job satisfaction. However, work-life balance does not have a significant effect on job satisfaction. Managerial implications based on results are an organitation has important role in work-life balance. Organizations can pay more attention to how employees control and manage their work in order to carry out their work effectively, identify and reduce the size of the level of job demands required for employees, as well as giving awards and encouragement at work that can lead to increased motivation that helps in reducing job stress.